Does government and corporate saving influence household saving in Finland? - Seppo Kostiainen; Christian Starck (Bank of Finland, 1990)
The aim of this paper is to empirically assess whether government and/or corporate sector saving influence aggregate household saving in Finland. The aim is carried out using quarterly data from the period 1960 - 1988. We use both a consumption function and an Euler equation approach, and both linear and nonlinear models are employed. We fail to document indications that household saving has been influenced by government or corporate sector saving during our sample period. Our findings suggest that households have behaved rationally on the whole in accordance with the basic permanent income hypothesis according to which government and corporate saving are not considered to be part of household disposable income. We furthermore find that a fraction of the households have been liquidity constrained, and that intertemporal substitution has been weak.
URN:NBN:fi:bof-201908061353
Keywords: 330